OPTIMALISASI PERENCANAAN PRODUKSI APLIKASI BETON GEOPOLYMER DARI FLY ASH DAN BOTTOM ASH BASIS DRY GEOPOLYMER DAN ANALISIS KELAYAKAN: OPTIMIZATION OF PRODUCTION PLANNING AND BUSINESS POTENTIAL ANALYSIS OF FLY ASH AND BOTTOM ASH-BASED GEOPOLYMER CONCRETE - Muhammad Faiz Shafiyurrahman (KURVATEK, 2025)
Dry geopolymer-based concrete from fly ash and bottom ash has been widely developed with the aim of advancing infrastructure to build a sustainable industry from the utilization of such waste. Planning for the construction of a concrete derivative product production business needs to be carried out to optimize the utilization of the budget, warehouse stock, and profit. The derivative products used in this study are paving blocks, adobes, and kanstin with compressive strength standards of 25 MPa, 10 MPa and 30 MPa respectively. Based on the compressive strength standard, the FA:BA ratio of each product is successively 3:1; 1:1; and 1:0 [1]. Therefore, the purpose of this study is to maximize profits by optimization production and raw materials based on calculations simplex linear programming method and conducting business feasibility studies using the SWOT method. Based on the calculation results, the business was focused on paving block products with a total production of 431 pcs/h. with total raw material needs of fly ash 1,199 tons / hour and bottom ash 0,399 tons / hour with a total profit of IDR 172,413. Based on the feasibility test of dry geopolymer concrete products using the SWOT method, it can be said to have great opportunities with its advantages.